B Cell Markers of Operational Tolerance Can Discriminate Acute Kidney Allograft Rejection From Stable Graft Function. Issue 5 (May 2015) - Heidt, Sebastiaan; Vergunst, Manon; Anholts, Jacqueline D.H.; Reinders, Marlies E.J.; de Fijter, Johan W.; Eikmans, Michael; Claas, Frans H.J.
Abstract : Background: Recently, several B cell–related markers have been described to be upregulated during operational tolerance in kidney allograft recipients. Little data exist on these markers during allograft rejection. Methods: In this study, we investigated regulation-associated B-cell phenotypes in peripheral blood mononuclear cells (PBMCs) of kidney transplant recipients with (n = 21) and without (n = 22) acute rejection (AR). We also determined expression levels of the B cell–related genes, MS4A1, TCL1A, and CD79B, in PBMCs and isolated B cells. Patient samples were analyzed before transplantation at discharge and at time of AR before initiation of antirejection therapy or at matching timepoints in patients with stable graft function. Results: On transplantation, the peripheral CD19 + CD24 hi CD38 hi transitional B cell subset strongly declined, regardless of the subsequent occurrence of AR. In contrast, the CD19 + CD27 + CD24 hi subset remained stable after transplantation in both patients groups. MS4A1 gene expression levels in PBMC were comparable between patient groups at all timepoints. In contrast, TCL1A expression levels increased in stable patients, but decreased in patients at the time of AR in both PBMC and isolated B cells. CD79B expression levels in stable patients were unaltered after transplantation in PBMC but showed an increase in the B cell fraction at discharge. At the time of AR, CD79B gene expression was significantly lower compared to stable patients, being most apparent in the B-cell fraction. Conclusion: These results suggest that, in addition to being markers for immunologic unresponsiveness, gene expression levels of TCL1A and CD79B may also identify immune activation in the setting of kidney transplantation. Abstract : Expression of TCL1A and CD79B on peripheral blood B cells may distinguish stable patients from those with acute rejection. Thus, B cell markers associated with tolerance may also be relevant for patients still requiring maintenance immunosuppression. Supplemental digital content is available in the text.